IMPLEMENTASI PERATURAN DAERAH NOMOR 03 TAHUN 2012 MENGENAI TEMPAT PEMAKAMAN UMUM DI KOTA PEKANBARU TAHUN 2014 - Surya Fernando; Muhammad Ridwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Indonesia embraced decentralization system in accordance with Law No. 32 of 2004 , in which the central government delegate / give up some power and authority to local governments to regulate and manage part of the authority and the power of the Unitary State of the Republic of Indonesia . One policy area in the city of Pekanbaru , issued a policy in the form of Regional Regulation No. 03 Year 2012 on Levy Funeral Service , incineration corpse . Burial in Pekanbaru itself pretty much covers have public , private and governmental . Remains of the many burial spread across 12 districts Pekanbaru , which is managed by the government is only six , but who has the appropriate regulations only two . Based on the description above, the authors are interested in doing research with the title